Controlled Release Bilayer Floating Effervescent and Noneffervescent Tablets Containing Levofloxacin and Famotidine - Tufail, Muhammad; Shah, Kifayat Ullah; Khan, Ikram Ullah; Khan, Kamran Ahmad; Shah, Shefaat Ullah; Rashid, Faisal; Khan, Jahangir; Alshammari, Abdulrahman; Alasmari, Abdullah F.; Riaz, Muhammad Shahid (International Journal of Polymer Science, 2024)
The present study is aimed at designing bilayer-floating tablets to improve the drug concentration in the stomach for enhanced therapeutic efficacy. The tablets are comprised of an upper layer of levofloxacin (466.5 mg) and a lower layer of famotidine (133.5 mg). Five formulations (F1-F5) were developed by using hydroxypropyl methylcellulose grades (K4M, K15M, and K100M) along with Carbopol 934. In the case of the effervescent system (F1-F3), sodium bicarbonate was added to impart buoyancy to the tablets; while in the case of noneffervescent formulations (F4 & F5), guar gum and xanthan gum were incorporated to induce flotation and swelling and retard the release of a drug. The precompression characteristics of tablets depict the suitability of all formulation powder for direct compression. The ATR-FTIR analyses have shown that the components of both effervescent and noneffervescent tablets are compatible with each other. The total weight of each tablet was 600 mg, with a weight variation of about ≤10 mg. Both the layers were smooth and flat with a thickness ranging from 3.16±0.04 to 3.54±0.01 mm. The diameters of prepared floating tablets were about 15 mm, optimum for oral administration. After adjusting the tablet’s hardness to 6-7 kg/cm2, its friability was found to be <0.35 percent. The mean drug content of the formulations was above 90%. The floating lag time of all formulations (F2-F5) was below 25 seconds, except F1 which took almost 50 seconds to start floating on the surface of gastric content due to its higher density. The total floating time of effervescent (F1-F3) and noneffervescent formulations was in the range of 15-25 hours, thereby providing sufficient time to complete drug release and absorption in the gastric area. The total floating time of noneffervescent formulations was higher (p≤0.05) than effervescent formulations due to efficient wettability and swelling characteristics. The release of drugs from both layers of noneffervescent tablets was significantly controlled when compared to the effervescent system, and an anomalous non-Fickian diffusion was found for the drug release. The stability study of the optimized formulation proved the integrity and stability of the developed formulation. Thus, developed formulations are deemed suitable for controlled codelivery of active pharmaceutical ingredients for the effective treatment of H. pylori.